Millimeter-Scale Zn(3-Ptz)2metal-Organic Framework Single Crystals: Self-Assembly Mechanism and Growth Kinetics - Herrera-Urbina, F; Singh, D; Enríquez-Montenegro, J; Vivas, L; Garcia-Garfido, J; Chi-Duran, I (American Chemical Society, 2021)
The solvothermal synthesis of metal-organic frameworks (MOFs) often proceeds through competing crystallization pathways, and only partial control over the crystal nucleation and growth rates is possible. It challenges the use of MOFs as functional devices in free-space optics, where bulk single crystals of millimeter dimensions and high optical quality are needed. We develop a synthetic protocol to control the solvothermal growth of the MOF [Zn(3-ptz)2]n (MIRO-101), to obtain large single crystals with projected surface areas of up to 25 mm2 in 24 h, in a single reaction with in situ ligand formation. No additional cooling and growth steps are necessary. We propose a viable reaction mechanism for the formation of MIRO-101 crystals under acidic conditions, by isolating intermediate crystal structures that directly connect with the target MOF and reversibly interconverting between them. We also study the nucleation and growth kinetics of MIRO-101 using ex situ crystal image analysis. The synthesis parameters that control the size and morphology of our target MOF crystal are discussed. Our work deepens our understanding of MOF growth processes in solution and demonstrates the possibility of building MOF-based devices for future applications in optics. © 2021 The Authors.